Non-linear oscillations in first order systems with delay. II. Non-autonomous case - Anh, Nguyen Dong; Khiem, Nguyen Tien (Vietnam Journal of Mechanics, 1990)
The influence of the periodic force on the nonlinear first order systems with delay is investigated by the asymptotic method Crulov-Bogoliubov-Mitropolski. A detailed research of the response of Duffing and Van der Pol systems to external periodic force is given. The obtained results are compared with well-known ones in such second order systems without delay.